The Impact of Talent Management on Employee Performance Mediated by Employee Engagement - Muhamad Ekhsan; Daspar; Ryani Dhyan Parashakti; Didin Hikmah Perkasa (East Asian Journal of Multidisciplinary Research, 2023)
The study aims to analyze the impact of talent management on employee performance through employee engagement mediation. The data was collected from 84 employees working in the manufacturing area of Bekasi using questionnaires as a data collection tool. This research uses a quantitative approach with survey methods. Respondents were selected from manufacturing companies in the Bekasi region through purposive sampling techniques. The data collected will be analyzed using Structural Equation Modeling (SEM) techniques to test hypotheses and evaluate models. These findings show that the implementation of good talent management can improve employee performance through increased employee engagement. Employee engagement also mediates the relationship between talent management and employee performance